SISTEM REKRUTMEN KARYAWAN PADA PT. BANK SYARIAH MANDIRI CABANG BONE - S, Arifin; Kara, Muslimin H; K, Amiruddin; AR, Moh. Sabri (Jurnal Diskursus Islam, 2017)
This artickel discusses the system of recruitment of an employee at PT Bank Syariah Mandiri Branch Bone. One of the activities that are important in the management of human resources is a recruitment of employees. If in terms of recruitment of insufficient surely will result in employees who are not qualified in accordance with the company's expectations. Subject matter in the study is how the system of recruitment, selection, and placement of an employee at PT Bank Syariah Mandiri Branch Bone. The purpose of this research is to know the system of recruitment of an employee at PT Bank Syariah Mandiri Branch Bone. This type of research is a qualitative descriptive study, methods of data collection consists of observation, interviews, and documentation, data processed with three stages namely reduction data, data verification and interpretation of the data by analysis approach sociological, and philosophical approach. The research found that the system 1) recruitment of employees at PT Bank Syariah Mandiri Branch Bone based on the analysis of the needs of employees, the recruitment process is carried out by means of: a) the preparation of the strategy of recruiting, b) search applicants-applicants, c) allowance for applicants-applicants that are not relevant or that don't match and the creation of groups of applicants. In the process of recruiting employees at PT Bank Syariah Mandiri Branch Bone yet it all fits with the theory that there is, especially in terms of employee experience more diutakan than the scientific background is concerned, have not put forward analysis feasibility and appropriateness with the Shariah-compliant management approaches include shiddi > q, ama > well, fat} a > well, and tabligh.